2021
DOI: 10.1021/acsami.1c03508
|View full text |Cite
|
Sign up to set email alerts
|

General Strategy to Fabricate Porous Co-Based Bimetallic Metal Oxide Nanosheets for High-Performance CO Sensing

Abstract: Two-dimensional (2D) porous bimetallic oxide nanosheets are attractive for high-performance gas sensing because of their porous structures, high surface areas, and cooperative effects. Nevertheless, it is still a huge challenge to synthesize these nanomaterials. Herein, we report a general strategy to fabricate porous cobalt-based bimetallic oxide nanosheets (Co–M–O NSs, M = Cu, Mn, Ni, and Zn) with an adjustable Co/M ratio and the homogeneous composition using metal–organic framework (MOF) nanosheets as precu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 63 publications
(127 reference statements)
0
34
0
Order By: Relevance
“…The sheets possess an ultra-high surface area of 220.7 m 2 g −1 , exposing abundant active sites. The sensor exhibited ppb level detection with room-temperature operation [ 94 ]. Jang et al developed subatomic level thick heterogeneous oxide SnO 2 /CoO x nanosheets for gas sensing.…”
Section: Salient Applications Of 2d Materialsmentioning
confidence: 99%
“…The sheets possess an ultra-high surface area of 220.7 m 2 g −1 , exposing abundant active sites. The sensor exhibited ppb level detection with room-temperature operation [ 94 ]. Jang et al developed subatomic level thick heterogeneous oxide SnO 2 /CoO x nanosheets for gas sensing.…”
Section: Salient Applications Of 2d Materialsmentioning
confidence: 99%
“…However, there is still an immense task to prepare these porous 2D nanomaterials. Qin et al [174] reported a general scheme to prepare 2D porous structure cobalt-based bimetallic oxide sheets (Co-M-O NSs, M = Cu, Mn, Ni, and Zn) with tunable Co/M ratio with homogeneous composition [133] Reproduced with permission. [174] Reproduced with permission.…”
Section: Two Dimensional-metal Organic Framework (2d-mof)mentioning
confidence: 99%
“…c) Temperature-dependent sensing response of Co−M−O NSs toward 100 ppm CO. d) Response and recovery time of Co−M−O NSs to 0.5−100 ppm CO. e) Dynamic response transition of Co−Mn−O NSs at 175 °C. TEM images of the f) Co−Cu−O NS, g) Co−Mn−O NS, h) Co−Ni−O NS, i) Co−Zn−O NS, j) XRD analyses of Co−Cu−O NS, Co−Mn−O NS, Co−Ni−O NS, and Co−Zn−O NS [174]. Reproduced with permission.…”
mentioning
confidence: 99%
“…35 The large specific surface areas of 2D MOFs can provide more proton jumping sites, and the highly open interlayer channels also allow guest molecules carrying protons to enter, which synergistically improves proton transfer effectiveness. 36 Inspired by the studies above, we focused on the development of newer 2D MOFs as efficient proton conductors.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, they have been applied in a wide variety of applications, including use as proton conductors. Two-dimensional (2D) MOFs have received an increasing amount of attention in recent years due to the exposure of the functional groups and the open interface . The large specific surface areas of 2D MOFs can provide more proton jumping sites, and the highly open interlayer channels also allow guest molecules carrying protons to enter, which synergistically improves proton transfer effectiveness . Inspired by the studies above, we focused on the development of newer 2D MOFs as efficient proton conductors.…”
Section: Introductionmentioning
confidence: 99%